STUDI TENTANG KECENDERUNGAN KECURANGAN AKUNTANSI PADA PT. UNI LOGISTIK INDONESIA - Agustina Sulistiyowati; Parju Parju (Serat Acitya, 2019)
This study aims to determine the influence of internal control systems, suitability of compensation, morality of management to the tendency of accounting fraud at PT. Union Logistics Indonesia. The tests were conducted at head office and 7 branch offices. This study used questionnaires with respondents consisting of managerial and finance section of 42 respondents.The results showed that the internal control system has a negative and significant effect on the tendency of accounting fraud.  Suitability of compensation has a negative and significant effect on the tendency of accounting fraud. Morality of management has an effect on negatively and significantly to the tendency of accounting fraud.Keywords: Internal control system, suitability of compensation, morality of management, tendency of accounting fraud.